The Predictive Role of Hand Section of Fugl–Meyer Assessment and Motor Activity Log in Action Research Arm Test in People With Stroke - Chen, Peiming; Liu, Tai-Wa; Tse, Mimi M. Y.; Lai, Claudia K. Y.; Tsoh, Joshua; Ng, Shamay S. M. (Frontiers in Neurology, 2022)
Background: Recent findings of clinical studies have demonstrated the significant positive relationship between Fugl-Meyer Assessment of Upper Extremity score and the Action Research Arm Test (ARAT) score in people with stroke. Although Motor Activity Log (MAL) can assess the self-perception of the motor performance, which can affect the performance of upper limb, the relationship between MAL score and ARAT score is still remained unclear. The objective of this study is to quantify the independent contribution of MAL scores and FMA-hand score on the ARAT scores in people with stroke. Methods: This is a cross-sectional study. There were total 87 subjects (50 males, 37 females; mean age=61.12±6.88 years old, post-stroke duration=6.31±2.84 years) included in this study. Self-perceived performance in using paretic limb was measured by MAL, including subscale of Amount of Usage (MAL-AOU) and Quality of Movement (MAL-QOM). Functional performance of upper limb was measured by Action Research Arm Test (ARAT). Upper limb motor control of hand was measured by hand section of Fugl-Meyer Assessment (FMA-hand). Results: The result showed that MAL-QOM (r=0.648, p<0.001), MAL-AOU (r=0.606, p<0.001), FMA-hand scores (r=0.663, p<0.001) and the use of a walking aid (r=-0.397, p<0.001) were significantly correlated with the ARAT scores. A total 66.9% of the variance in the ARAT scores was predicted by the final regression model including MAL-QOM, MAL-AOU, FMA-hand scores and walking aid. The FMA-hand score was the best predictor of ARAT scores, which can predict 36.4% variance of ARAT scores in people with stroke, when controlled the effect of using a walking aid. After controlling for use of a walking aid and FMA-hand scores, the multiple linear regression modeling showed that MAL-QOM and MAL-AOU scores could also independently predict an additional 10.4% of the variance in ARAT scores. Conclusion: In addition to FMA-hand score, MAL score was significantly correlated with the ARAT score. Improving self-perceived performance should be one goal of rehabilitation in people with stroke. Further work developing and testing techniques to do so is clearly warranted.